IMPLEMENTASI ATURAN WALIKOTA DENPASAR NO. 11 TAHUN 2005 TERKAIT PENGELOLAAN RETRIBUSI PARKIR DI TEPI JALAN UMUM DALAM MENINGKATKA PENDAPATAN ASLIDAERAH PADA PASAR MALAM TERMINAL KRENENG DENPASAR - Ida Bagus Indra Bhaskara; Ni Ketut Sari Adnyani; Dewa Bagus Sanjaya (Universitas Pendidikan Ganesha, 2023)
The purpose of this study is to determine the management of parking levies by Transportation Departement in increasing local revenue (PAD) of Denpasar City at Kreneng Market and to find out the obstacles faced by Transportation Departement in managing parking levies at Kreneng Market in Denpasar due to the implementation of Denpasar Mayor Regulation No 11 of 2005. This study used empirical legal research with a descriptive research nature. This study is conducted at Kreneng market in Denpasar. Descriptive qualitative is used as a data processing and analysis technique in this research. The result of the study revealed that the management of parking leavis by Transportation Departement is quite effective, where the target number of parking levies on the of public roads in Denpasar is based on the large number in Denpasar. It is calculated from the number of vehicle capacities at each parking points and the number of vehicles that comes and go at the parking lot. The target setting for roadside parking levies has alsoe been distributes in each parking point. Meawhile, there are some obstacles face by Transportation Departement in managing parking levies at Kreneng Market in Denpasar that caused the effectiveness decreased such as user ignorance, revenue leakage, lack of society awareness, resusrance from certain parties, and the limitation of infrastructure and technology.